Tensile strength of compacted soil - Lee, Wen Yan (2018)
Tensile strength of soil is important for many earth slopes and retaining structures. With the formation of tensile cracks, the permeability of soils is greatly increased, and it can result in the failure of the earth retaining structures during raining periods. However, despite its importance, tensile strength is seldom investigated. There are a number of tests to determine the tensile strength and they can be divided into either direct or indirect methods. In direct methods, tensile load is imposed onto the specimen while in indirect methods, compressive load is imposed onto the specimen. This project aims to investigate the parameters that affect the tensile strength of compacted soil. Bukit Timah residual soil is used in this project and parameters such as degree of saturation, soil fabric and compaction methods are investigated. Laboratory tests were conducted to examine the tensile strength of compacted soil over a range of water content (19% – 26%) using the Brazilian tensile test (ASTM D3967-16, 2012) and the unconfined penetration test. Four series of test were conducted. Test series 1 and 2 consists of specimens that were compacted using dynamic and static compaction, respectively. The results were compared to investigate the effect of different compaction methods on the tensile strength of compacted soil. The results concluded that dynamic compaction produces soils that have a higher tensile strength as dynamic compaction produces a more flocculated soil structure. Test series 3-1 and 3-2 consists of specimens that were dynamically compacted at 24.2% (W4) and 26% (W5), respectively. The specimens were subsequently dried to other water contents before testing using the Brazilian tensile test. The results concluded that tensile strength is affected by both degree of saturation and dry density, where lower degree of saturation and higher dry density lead to a higher tensile strength. The effect of soil fabric was investigated by comparing the test results from Test Series 3-1 and 3-2 with Test series 1. The results revealed that a dispersed soil structure resulted in a higher tensile strength. The test results from Brazilian tensile test and unconfined penetration test were compared and revealed that the tensile strength obtained from the two tests are similar. The test results were also compared to the results in Kim et al. (2012) and Fang and Chen (1972) and it is concluded that the test results in this study follows the observed trend, where the tensile strength obtained from both test is in good agreement.